Quality of life among beta-thalassemic major children presented at Federal Government Hospital Islamabad, Pakistan - Bukhari, GulMehar Javaid (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the quality of life among beta-thalassemic major children in a tertiary care setting. Method: The cross-sectional descriptive study was conducted at the Federal Government Hospital, Islamabad, Pakistan, from October to December, 2020, and comprised beta-thalassemic major children aged 7-13 years. Socio-demographic information was collected using a questionnaire, while the quality of life was assessed using a pretested tool with Cronbach’s alpha value 0.855. The data was analysed using SPSS 25. Results: Of the 87subject, 47(54%) were males and 40(46%) were female. The overall mean age was 10.71±1.99 years. The mean quality of scale score was 50.24±18.88. Poor quality of life was found among 33(37.9%) children. The quality of life had significant association with age 7-9 years, male gender and blood transfusion frequency 2 or more (p<0.05). The adjusted odds were also significant with age and blood transfusion frequency (p<0.05). The overall mean score was significantly related within age groups and frequency of blood transfusion (p<0.05), whereas physical and emotional domains were significant with age (p<0.05), while the four domains of physical, psychological, social and educational were associated with frequency of blood transfusion (p<0.05). Conclusion: Quality of life among thalassemic children was found to be considerably low. The physical and emotional domains need to be focussed upon for improving the quality of life. Measures should be taken to avoid the increased need of blood transfusions through treatment compliance. Key Words: Beta-thalassemia major, Quality of life, QoL, Blood transfusion.